(untitled) (Research, Society and Development, 2025)
Objective: To evaluate the nutritional status and its association with the prevalence of gastrointestinal symptoms in palliative care (PC) patients. Methodology: An analytical cross-sectional study conducted between May and September 2023. Socioeconomic, demographic, clinical history, and anthropometric data were collected. Descriptive analysis was performed, presented in absolute and relative frequencies for categorical variables. For continuous variables, the mean and standard deviation or the median and interquartile range were used. Normality deviations were checked using the Shapiro-Wilk test. One-way ANOVA or Kruskal-Wallis tests were applied. Fisher’s Exact test was also performed. A 5% significance level was used for all tests. Results: Upon evaluating 55 patients in palliative care, no significant associations were found between nutritional status and the incidence of gastrointestinal symptoms. However, a higher prevalence of gastrointestinal symptoms was observed in the underweight group. Among the gastrointestinal symptoms, the most prevalent were: presence of intestinal gas 52.7% (n=29), flatulence 47.2% (n=26), discomfort from gas 44.6% (n=21), and abdominal distension 34.5% (n=19). Underweight was found in 45.4% (n=25) and eutrophy in 38.1% (n=21) of the patients. The lowest means for weight, Body Mass Index (BMI), and arm circumference adequacy (AC) were found in the underweight group (p<0.001). Conclusion: The nutritional status of patients in palliative care was not associated with the occurrence of gastrointestinal symptoms.